Ludic activities and improving English speaking skills among bachillerato students at a public institution in Loja city. School year 2022-2023. Actividades lúdicas y mejora de la habilidad oral en inglés en los estudiantes de bachillerato de una institución pública de la ciudad de Loja. Año escolar 2022-2023. - Saavedra Ortiz, Nayely Estefanía (2023)
This research is aimed to enhance the English speaking skills by using ludic activities among bachillerato students at a public institution in Loja city during the school year 2022-2023. Speaking skill is one of the most vital abilities to acquire since it is an interactive process that allows participants to communicate information. Speaking is known as a “productive skill” which means that students have to produce the language. There have been a variety of researchers that displayed the importance of applying several strategies to improve oral ability. However, there is still a gap in students’ speech for that reason this research was conducted to find a solution to this issue. Furthermore, this research used an action research design with a mixed method approach to gathering quantitative (scores) data through the use of a pretest and posttest, and qualitative (perceptions) data through the use of a questionnaire. The data demonstrated that students had a noticeable improvement in each speaking component fluency, coherence, accuracy, pronunciation, and vocabulary in which they were measured. This result was corroborated by the scores of the posttest which indicated students had an achievement of 8.12/10 which is above the general score. From this, it could be concluded that the applications of specific ludic activities had a huge impact on students' speaking skills. More specifically, students attain a higher score in vocabulary which indicates that ludic activities positively impact expanding their glossary. Additionally, these ludic activities helped the pre-service teacher to have a great view of the advantages of applying new innovative strategies as ludic activities to improve learners’ performance. Keywords: English language, ludic activities, speaking skills.